A tangibilização da estratégia: a perspectiva do Design estratégico como apoio à execução da estratégia empresarial - Wolfarth, Juliana (Universidade do Vale do Rio dos Sinos, 2015)
This study discusses how a strategic design-based approach can support strategy execution, contributing to its tangibilization. To do so, it is reviewed the concept of strategy, typically addressed by administration area, through strategic design approach. In that perspective, strategy means the way the company presents itself to the market through a set of distinctive organizational activities that create a unique mix of value, in the form of a value creation system that operates in the generation of meaning effects. Strategic design resignifies the concept, subtracting any temporal resolution, but giving it a continuously and indefinitely strategic act. Tangibilize strategy, or support its execution, therefore, envolves collaborative meaning creation between what is avowed as strategy and what is executed. Based in these assumptions, this study seeks to attend its objective, through an action research whose unit of analysis is a private university. The methodology contemplate one action research cycle with four steps, in which diverse data collect technique were used, allowing data triangulation. The results were built over all the action research cycle. Starting from a diagnosis of strategy process in the company, many information were raised to foment a design process, which resulted in three purposes on strategy execution support. The three purposes were evaluated by the company, and the best evaluated was evolved until a conceptual solution to respond the study objective. The results also point to strategic design potentialities to act in strategy elaboration and execution, specially having focus on workforce engagement and involvement.
Keywords: Estratégia; Design estratégico; Execução; Tangibilização; Strategy; Strategic Design; Execution; Tangibilization; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial